UJI EFEKTIVITAS NUCLEAR POLYHEDROSIS VIRUS (NPV) TERHADAP PENGENDALIAN HAMA PENGGEREK BATANG JAGUNG Ostrinia furnacalis Guenee (LEPIDOPTERA:PYRALIDAE) PADA BERBAGAI INSTAR DI LABORATORIUM - Tri Yaninta Ginting; Syahrial , Oemry; Mukhtar Iskandar Pinem (Jurnal Agroekoteknologi, 2014)
Researech on title test of efectivity nuclear polyhedrosis virus on controlling corn borerOstrina furnacalis Guenee (Lepidoptera:Pyralidae) on some instar in the laboratory. The researchaim to know the concentrate of NPV on some instar of corn borer controlling in the laboratory.This research used randomized complete design factorial with two factor, i.e. instar of larva (3, 4and 5) and dose of NPV (0, 1000, 2000, and 3000 ppm) with three replications. The results showedthat the highest percentage of mortality was 86,08% (virus dose 3000 ppm) and the lowest was7,52% (control) .Keywords : NPV, mortality, Ostrinia furnacalis Guenee